Late Gadolinium Enhancement by Cardiac Magnetic Resonance and Speckle Tracking Echocardiography in the Evaluation of Cardiac Complications in Chagas Cardiomyopathy: A Systematic Review - Laura-M Romero Acero; Andrés-D Gallego Ardila; Michele Nanna; Frida T Manrique Espinel; Héctor M Medina; Esteban Sciarresi; Fabio-A Tabares-Mora; Alejandro Olaya Sanchez; Carolina Ayala; Jorge L Fajardo Ruge; Ramón Medina-Mur; Diana Vargas Vergara; et al. (Reviews in Cardiovascular Medicine, 2022)
Background: Chagas cardiomyopathy (CC) increases cardiovascular mortality associated with congestive heart failure (CHF), ventricular arrhythmias (VA), and sudden cardiac death (SCD). Different imaging techniques have been tested to assess disease progression and cardiac risk in individuals with Chagas disease (ChD). In this systematic review, we evaluated the accuracy in detecting cardiac complications in CC patients using cardiac magnetic resonance (CMR) and speckle tracking echocardiography (STE). Methods: A search was done on PubMed, Cochrane, and Embase for studies in humans over 18 years of age with ChD. Demographic data, research methodology, imaging parameters, and cardiac outcomes were extracted, and study quality was assessed, resulting in a narrative description. Results: Twelve studies with 1124 patients were analyzed. One study discovered a contractility pattern by STE. Four studies assessed the identification of Early Cardiac Impairment (ECI) and VA risk, respectively, while three studies evaluated the risk of SCD. Global Longitudinal Strain (GLS) identified patients with ECI (–18.5 ± 3.4% non-fibrosis vs –14.0 ± 5.8% fibrosis, p = 0.006 and –18 ± 2% non-fibrosis vs –15 ± 2% fibrosis, p = 0.004). The amount of fibrosis >11.78% or in two or more contiguous transmural segments were markers for VA risk. GLS and the amount of fibrosis were found to be predictors of SCD. Conclusions: STE may be considered a screening technique for identifying the subclinical status of CHF. CMR using Late Gadolinium Enhancement (LGE) is considered a relevant parameter for stratifying patients with ChD who are at risk of SCD. Fibrosis and GLS can be used as markers to categorize patients at risk for arrhythmias.